Retraction of health science articles by researchers in Latin America and the Caribbean: A scoping review - Herrera-Añazco, Percy (2024)
We aimed to conduct a scoping review to assess the profile of retracted health sciences articles authored by individuals affiliated with academic institutions in Latin America and the Caribbean (LAC). We systematically searched seven databases (PubMed, Scopus, Web of Science, Embase, Medline/Ovid, Scielo, and LILACS). We included articles published in peer-reviewed journals between 2003 and 2022 that had at least one author with an institutional affiliation in LAC. Data were collected on the year of publication, study design, authors' countries of origin, number of authors, subject matter of the manuscript, scientific journals of publication, retraction characteristics, and reasons for retraction. We included 147 articles, the majority being observational studies (41.5%). The LAC countries with the highest number of retractions were Brazil (n = 69), Colombia (n = 16), and Mexico (n = 15). The areas of study with the highest number of retractions were infectology (n = 21) and basic sciences (n = 15). A retraction label was applied to 89.1% of the articles, 70.7% were retracted by journal editors, and 89.1% followed international retraction guidelines. The primary reasons for retraction included errors in procedures or data collection (n = 39), inconsistency in results or conclusions (n = 37), plagiarism (n = 21), and suspected scientific fraud (n = 19). In conclusion, most retractions of scientific publications in health sciences in LAC adhered to international guidelines and were linked to methodological issues in execution and scientific misconduct. Efforts should be directed toward ensuring the integrity of scientific research in the field of health.